How do I teach this kid? : visual work tasks for beginning learners on the autism spectrum - Henry, Kimberly A. 4 0 16; 5 (Arlington, Texas : Future Horizons, 2005)
Ideas for over 80 independent tasks are presented for teaching autistic children, including sorting, matching, reading, writing, mathematics, and motor tasks.
Professional.
Keywords: 2 -- 0; 6; Education.;education. -- Autistic children;Special education.;Autistic Disorder;Education, Special.;Child.;Autism.; 20; 2